Thailand - Stads, Gert-Jan; Omot, Norah; Bandrapiwat, Isiwat; Nin-Pratt, Alejandro; Nguyen, Pham Thi; Thaingam, Jintawee (International Food Policy Research Institute, 2020)
Agricultural research investment in Thailand rose gradually during 2013–2017, largely driven by increased spending by the country’s livestock, forestry, and rice departments.